A morphometric study of glia and neurons in the anterior cingulate cortex in mood disorder. - Gittins, R; Harrison, P (2011)
BACKGROUND: The anterior cingulate cortex (ACC) is a key region for the pathophysiology and treatment of depression. However, it remains unclear whether and how the morphology of the ACC is altered in subjects with mood disorders. METHOD: A post mortem morphometric study of the supragenual ACC (Brodmann area 24b) in seven subjects with mood disorder and nine comparison subjects. We measured glial and neuronal density, and neuronal size and shape. We also quantified the astrocytic marker, glial fibrillary acidic protein (GFAP), using immunoautoradiography. RESULTS: Cortical and layer thickness did not differ between groups. Subjects with mood disorder had a decreased density of glial cells across all layers, and a reduction in GFAP in white matter. The density of pyramidal neurons was decreased selectively in layer Vb, and their size was increased in layers V and VI. The shape of pyramidal neurons also differed in mood disorder, in layers Va and VI. CONCLUSION: These data provide further evidence for morphometric alterations in glia and pyramidal neurons in mood disorder. They represent a possible cellular basis for the aberrant functioning and connectivity of the ACC apparent from neuroimaging and other studies.